SMART LIVING TECHNOLOGY DALAM ADMINISTRASI ONLINE DI JAKARTA - Maheswari, Hafizhah; Berliana Putri, Kalista; Aura Pradipta, Zhafira; Darmawan, Ivan (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
This study aims to analyze the implementation of Smart Living Technology in supporting online administrative services in Jakarta. This research uses a case study method by utilizing secondary data from various official portals of the Jakarta Provincial Government, such as Alpukat Betawi, PTSP Online, Pajak Online, and JAKI. The focus of the study is to evaluate the effectiveness of web-based information systems in improving the efficiency of public services. The analysis process follows the waterfall method to understand the development and implementation of these information systems. The findings show that web-based online administrative services in Jakarta have facilitated public access, improved work efficiency, and promoted administrative transparency. These conclusions support that the implementation of Smart Living Technology in Jakarta is feasible to be further developed as part of continuous public service digitalization efforts.